Mathematical modelling of core regulatory mechanism in p53 protein that activates apoptotic switch. (7th February 2019) - Chong, Ket Hing; Samarasinghe, Sandhya; Kulasiri, Don; Zheng, Jie
Highlights: Extended model of Chong (2015) and Zhang (2009) for p53 activation of apoptosis. Incorporation of the apoptosis initiation module involving Puma, Bcl2 and Bax. Activation of Bax with an all-or-none response as an indicator for apoptosis. The p53 apoptosis model shows ATM's auto-activation dictates cell fate decisions. Prediction of Puma gene therapy in cancer cells overexpressing Bcl2. Abstract: The p53 protein, a tumour suppressor, is a key player in the DNA damage response. The activation of apoptosis by p53 involves the intrinsic apoptotic pathway to eliminate stressed cells that contain DNA lesions. Recent experiments have found that apoptosis happen in an all-or-none switch like manner (Albeck et al., 2008; Rehm et al., 2002). We focus on modelling the mechanism of p53 activation of apoptosis in response to sustained high DNA double-strand breaks. The aim of the research is to investigate the design principles behind the regulation of p53 activation of apoptotic switch. Building on previous models (Chong et al., 2015; Zhang et al., 2009a), we developed a mathematical model that incorporated the molecular interactions in the core regulation of p53 and the apoptosis initiation module involving Puma, Bcl2 and Bax. Activation of Bax was assumed to be an indicator of apoptosis initiation. Chen et al. (2013) suggested that one of the components in the p53 pathway may control a threshold activation of apoptosis. We hypothesized that ATM auto-activation is the component that controls p53 threshold activation of apoptosis with ATM's multi-site autophosphorylation depending on damage intensity. The constructed model demonstrated how molecular interactions and stress signalling molecule ATM's auto-activation of the p53 network dictate cell fate decisions. Our simulation results are qualitatively consistent with the experimental findings of all-or-none activation of apoptosis and predicted overexpression of Bcl2 as a factor in causing malfunction of the apoptotic switch. We present a simplified yet plausible model of molecular mechanism that controls p53 activation of apoptotic switch.